PENGARUH KOMUNIKASI DAN PEMBINAAN TERHADAP KINERJA PENGURUS TIM PENGGERAK PEMBERDAYAAN KESEJAHTERAAN KELUARGA KANTOR CAMAT TANJUNG HARAPAN KOTA SOLOK - Yulia Sentosa; Nurhayati Nurhayati (LP2M Universitas Bina Bangsa, 2022)
This research was conducted at the Tanjung Harapan District Office, Solok City. The purpose of this research is to find out how much influence Communication and Coaching has on the performance of the Management Team for Family Welfare Empowerment. In this study, the population was the management of the Family Welfare Empowerment Team, which consisted of 33 people. The type of research is quantitative and the sampling technique uses the total sampling method or probability sampling. The data collection technique used is by using a questionnaire/questionnaire. Based on multiple linear regression analysis of the variables Communication and Coaching affects the performance of the Management Team for Family Welfare Empowerment Y = -2.662 + 0.925X1 + 0.148X2 + e. From the t-test that was carried out, it was found that the variable X1 Communication had a significant effect on the performance of the management with t count 14,482 < t table 2.04 and sig. (0.000) < 0.05. Then Ha is accepted and H0 is rejected. Variable X2 Coaching has a significant effect on Management Performance, the value is known to be t count 2.111 > t table 2.04 and sig, (0.043) < 0.05. Then Ha is accepted and H0 is rejected. From the f test, it was found that communication and coaching had a simultaneous effect on management performance with f count 111,860 > f table 3,316 and significance (0.000 < 0.05). Then H0 is rejected and Ha is accepted. From the Determination Test the R Square value is 0.882. This means that the contribution of the influence of the independent variable on the dependent variable is 88.2%, while the remaining 11.8% is influenced by other variables